Scaling boundaries - Šuligoj, Julija (Retrospektive, 2025)
The female body has been idealized, objectified, and burdened with contradictions throughout history. From ancient depictions to contemporary sports culture, it stands at the intersection of social norms and individual power. This paper explores the ambivalence toward the female body through the perspectives of medicine, art, and sports with an emphasis on mountaineering, highlighting how women, despite their achievements, faced and still face persistent scrutiny and bias. It focuses on the historical construction of the body, fashion’s role, and how physical activity shaped perceptions of femininity. The analysis shows how enduring stereotypes influence women’s participation in public life and sports to this day.
Keywords: bodily ambivalence; body history; družbene norme spola; female body; feminism; feminizem; gender norms; gorništvo; mountaineering; objectification; objektifikacija; sport; šport; telesna ambivalenca; zgodovina telesa; žensko telo